Comparative Study : The Effectiveness of Learning Japanese Using Duolingo and YouTube - Nurbadillah Nurbadillah; Indra Maki Wiguna; Saniyyah Wafa Nurjihan; Nafis Faturrahman; Humannisa Rubina Lestari (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This research looks into how well Duolingo and YouTube help people learn Japanese. A quantitative approach was taken, gathering information from 35 individuals through an online questionnaire. Participants were chosen based on whether they used Duolingo, YouTube, or both platforms. The questionnaire explored their past learning experiences, how they use these platforms, their preferences, how effective they think these tools are, and what challenges they encountered while learning. The findings reveal that most of the participants already had some background in Japanese and preferred online resources due to their accessibility, no cost, and fun features. Duolingo was liked for its organized, game-like approach, whereas YouTube was appreciated for its authentic, visual materials. A lot of people enjoyed learning at their own pace, finding listening and pronunciation to be useful strategies. Some individuals struggled with staying motivated and dealing with complicated grammar rules. To sum up, both Duolingo and YouTube are good resources for learning basic Japanese, especially for those studying on their own. However, they work best when used alongside other resources. It is suggested to combine digital tools with guidance from teachers for the best outcomes.